2018
DOI: 10.1016/j.hal.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Remote quantification of Cochlodinium polykrikoides blooms occurring in the East Sea using geostationary ocean color imager (GOCI)

Abstract: Accurate and timely quantification of widespread harmful algal bloom (HAB) distribution is crucial to respond to the natural disaster, minimize the damage, and assess the environmental impact of the event. Although various remote sensing-based quantification approaches have been proposed for HAB since the advent of the ocean color satellite sensor, there have been no algorithms that were validated with in-situ quantitative measurements for the red tide occurring in the Korean seas. Furthermore, since the geost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 29 publications
2
36
0
Order By: Relevance
“…. , 16:00 hours and in this case, the reference is the value at 13:00 hours, that is, x reference = X 13:00 . The R∆ t [%] is an indicator of uncertainties that are expected depending on the time of the day, assuming no changes in the in-water properties due to biological or biogeochemical processes.…”
Section: Diurnal and Day-to-day Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…. , 16:00 hours and in this case, the reference is the value at 13:00 hours, that is, x reference = X 13:00 . The R∆ t [%] is an indicator of uncertainties that are expected depending on the time of the day, assuming no changes in the in-water properties due to biological or biogeochemical processes.…”
Section: Diurnal and Day-to-day Variabilitymentioning
confidence: 99%
“…A variety of algorithms have been developed that utilize GOCI spectral observations to retrieve water-column constituents, including concentrations of the phytoplankton pigment chlorophyll-a (Chl-a) and total suspended material (TSM) [11][12][13]. GOCI data have also been used to determine the diurnal submesoscale variability of turbidity fronts [14], internal waves [15], red tides and green algae [16,17]. The success of GOCI has prompted the development of future GEO missions such as GOCI-II, scheduled to be launched in 2019, and formulation studies on a European geostationary satellite Ocean Color Advanced Permanent Imager (GEO-OCAPI).…”
Section: Introductionmentioning
confidence: 99%
“…Intensive efforts have been made in some countries to detect with satellites specific blooms of the two species evaluated in this research: Cochlodinium sp. (Noh et al, 2018) and Lepidodinium chlorophorum (Jegou, 2013;Morozov et al, 2013;Sourisseau et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Having a high degree of spatial and temporal coverage over a large scale is convenient for monitoring HABs. Several studies have shown distributions of HABs using satellite imagery and chlorophyll a (Chl- a ) concentration measurements [ 7 , 8 ]. Chl- a concentration in water is a major indicator of a trophic state and oceanic Chl- a concentration is the most common property characterizing first trophic levels in marine environments [ 9 ].…”
Section: Introductionmentioning
confidence: 99%